Active Learning in an Undergraduate Precalculus Course: Insights from a Course Redesign. Issue 3 (28th May 2021) - Gruber, Sean; Rosca, Raluca I.; Chazan, Daniel; Fleming, Elizabeth; Balady, Steve; VanNetta, Catherine; Okoudjou, Kasso A.
Abstract : Addressed toward course coordinators and departmental leaders interested in redesigning an undergraduate mathematics course, we highlight the steps our team at the University of Maryland, College Park has taken in bringing active learning to our Precalculus course. We provide examples of ways in which we have coordinated active learning across redesigned sections, as well as preliminary results of the effects of active learning on student success. Finally, given the broad set of experiences and backgrounds of our team members, we argue for the unique insight our redesign offers in restructuring a gatekeeper mathematics course to be focused on active learning.